When upward social mobility leads to frustration: Boudon's game-theoretic model of relative deprivation and experimental evidence. (February 2020) - Otten, Kasper
Highlights: The relationship between social mobility and frustration is examined. A game-theoretic model of relative deprivation is studied and experimentally tested. Improvements in social mobility can paradoxically increase frustration.